(untitled) (Research, Society and Development, 2025)
Cross-contamination in shared equipment represents a critical risk to the quality and safety of sanitizing products, as it may compromise subsequent batches and lead to regulatory non-conformities. To mitigate this problem, cleaning validation emerges as an essential strategy, providing scientific evidence of the effectiveness of industrial reactor sanitation. Thus, the objective of this study was to evaluate the effectiveness of a validated cleaning method applied to a 3000-L mixing reactor used in the production of sanitizing products. The methodology involved visual inspection, microbiological assessment by swab sampling, and physicochemical analyses (pH, apparent color, free chlorine, and quaternary ammonium compounds) after production cycles with three high-challenge products. The results showed no visible residue, microbiological counts below 1 CFU/cm², and stable physicochemical parameters with no indication of chemical residues, including quaternary ammonium levels below the limit of quantification. It is concluded that the validated cleaning method is effective, reproducible, and suitable for preventing cross-contamination, thus strengthening process safety and compliance with regulatory requirements.